Development of slow-release and thickening microencapsulated polymers for oil recovery - GONG Jincheng; SHU Qinglin; YUAN Fuqing; XU Hui; DONG Wen; SONG Qian (Youqi dizhi yu caishoulu)
In order to solve the problems of high injection resistance and large shear viscosity loss in polymer flooding agents， the microencapsulated polymers with slow-release and thickening properties were prepared by inverse emulsion polymerization and in situ polymerization with polyurethane prepolymer as the shell material and polymer as the core material. The formulation of the emulsion and the parameters for the preparation of the polymer core and the microcapsule shell were determined by a single factor experiment. A stable inverse emulsion was formed under the conditions of a compound emulsifier with an HLB of 6.4， an oil volume ratio of 50%， and an emulsifier dosage of 10%. Under the conditions of 45% aqueous monomer dosage， certain initiator dosage （0.04% of polymeric monomer）， reaction temperature of 45 °C， and reaction time of 4.5 h， polymer core materials were prepared with a monomer conversion rate of 98.44% and an apparent viscosity of 13.37 mPa·s in the solution. Under the conditions of a shell material mixing rate of 800 r/min， reaction temperature of 50 °C， reaction time of 4 h， and shell-to-core ratio of 1∶4， microencapsulated polymers were prepared. The surface of the microcapsule shell was smooth and intact， with high sphericity. The characterization results show that the infrared spectrum of the microencapsulated polymer contains characteristic peaks of both polymer and polyurethane， indicating that polyurethane microcapsules have achieved the encapsulation of the polymer. The particle size of microencapsulated polymers is mainly distributed between 300 nm and 500 nm， and the median particle size is 368 nm， with good uniformity and sub-micron size. The initial viscosity of microencapsulated polymers in water is 0.5 mPa·s， which increases to 12.57 mPa·s after 5 d. The viscosity retention rate after 90 days is 94.99%， indicating good slow-release and thickening properties and thermal stability. When the shear speed is 12 000 r/min， the viscosity retention rate of microencapsulated polymers is 98.25%， indicating good shear resistance.